Pengaruh Firm Size, Leverage, Audit Fee, Dan Audit Tenure Terhadap Opini Audit Going Concern (Studi Pada Perusahaan Perbankan Terdaftar Bursa Efek Indonesia 2018-2022) - Jessica Angeline Cokro; Riadi Riadi; Christoperleo Andelim; Siti Aisyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aim to examine the effect of Firm size, Leverage, Audit Fee, and Audit Tenure on going concern audit opinions. This research is a quantitative study with secondary data obtained from financial statements and audit reports of banking companies listed on the Indonesia Stock Exchange from 2018 until 2022. The sample of research is 30 banking companies that was carried out using a purposive sampling method and processed with IBM SPSS version 26. The analysis technique used is multiple linear regression. The results of study indicate that Firm Size has significant effect on going concern audit opinion, Leverage and Audit Fee have no significant effect on going concern audit opinion, and Audit Tenure has significant effect on going concern audit opinion.